Analysis of the effect of neuroendoscopy-assisted microscopy in the treatment of Large (Koos grade IV) vestibular schwannoma - Yang, Zhenxing; Xiong, Xiaoxing; Jian, Zhihong; Du, Li (Frontiers in Oncology, 2023)
Objective: This article aimed to investigate the effects of the endoscopic-assisted microsurgery technique on the resection of large (Koos grade IV) vestibular schwannoma (VS), as well as providing analysis of the prognosis of the patients. Methods: A retrospective analysis of the use of endoscopic-assisted microsurgery technique in 16 cases of large vestibular schwannoma surgery was carried out. Intraoperative nerve electrophysiological monitoring was conducted in order to explore the effect of neuroendoscopy on the resection of internal auditory canal tumors, protection of the facial nerve, and the effect of reducing postoperative complications. Results: Tumors were completely removed in all the 16 cases, and the facial nerve was anatomically preserved in 14 cases (87.5%). There was no postoperative cerebrospinal fluid leakage and no intracranial infection complications occurred. In accordance with the House-Brackmann (H-B) grading system, post-operative facial nerve function was grade I in 5 cases, grade II in 6 cases, grade III in 3 cases, and grade V in 2 cases. As a result, the preservation rate of facial nerve function (H-B grade I-II) was 68.8%. All 16 patients were followed up for 3 to 24 months, and no tumor recurrence was found on enhanced MRI. Conclusion: Using the endoscopic-assisted microsurgery technique in the retrosigmoid approach has many advantages over microscopic only approach. When compared to microscopy only approach, endoscope can provide a wide-angle surgical field superior to that of a microscope in areas such as the internal auditory canal in the resection of large VS, minimize iatrogenic injuries, ensure a complete removal of internal auditory canal tumors, and well as reducing postoperative complications such as cerebrospinal fluid leakage and the loss of facial and auditory nerve functions. Keywords: Vestibular Schwannoma; Neuro Conclusion: Through the retrosigmoid approach adopts neuroendoscopy combined with microscope surgery, which can make up for the dead angle of the microscope in the anatomical area such as the ICA in the resection of medium and large VS, minimize surgical traction damage, and completely remove ICA tumors. reduce the occurrence of complications such as cerebrospinal fluid leakage and protect the facial and auditory nerve function.